Detection of Biofilm Producing Bacteria causing Co-infections with Leishmania Ulcers and their Relation with Matrix metalloproteinase-13 Enzyme - Dhari, Abrar Kareem; Abed, Suha Maher; Abed, Ali Mohammed (Tikrit Journal of Pharmaceutical Sciences, 2024)
Background: Protozoan parasite causes Cutaneous Leishmaniosis (CL), dermatological disorder. Infected female phlebotomus sand flies spread these parasites. Secondary bacterial infection can worsen tissue damage and scarring. Objectives: In order to accurately ascertain the incidence of secondary bacterial infection caused biofilm formation in cutaneous leishmaniosis, it is imperative to investigate the significant immunological alterations by quantifying the levels of human Matrix metalloproteinase -13 (MMP-13). Materials and Methods: This study included 90 samples (20 controls and 70 CL sufferers). Study participants ranged in age from 3 months to 65 years, including both genders. Human Matrix metalloproteinase -13 measured by ELISA technique. Ulcer exudates were collected with sterile swabs after non-ulcerated lesions scraped. The specimens were cultured on Blood Agar, MacConkey Agar, Mannitol Salt Agar,and Hi Chrom Acinito. Laboratory methods were identified biofilm producing microorganisms. Results: Biofilms- forming secondary bacterial infections were found in 30 (42.8%) of 70 cutaneous Leishmaniosis patients. Bacterial from lesions Acinetobacter baumanni (8) cases (26.6 %), Acinetobacter lwoffi, Crobactor, Klebsiella, Proteus mirabilis, Proteus vulgaris, Pseudomonas Luteola, Raoultella, Serratia, Sphingo, (1) cases (3.3 %) for each spp. Pantoea (2) cases (6.6 %), Pseudomonas fluorescence (3) cases (10 %), and the study found no differences in MMP-13 levels in CL patients (5.7 + 0.2) compared to the control group. Conclusions: This study observed no differences in the average concentration in level of MMP-13 patient with CL compared with control groups.